"Politics and political elites in Latin America, challenges and trends" - Sendra, Mariana (Revista Española de Investigaciones Sociológicas, 2024)
Es reseña de: Politics and political elites in Latin America: challenges and trends / coord. por Manuel Alcántara Sáez, Mercedes García Montero, Cristina Rivas Springer Suiza, 2020. Latin American Societies. <acronym title="International Standard Book Number" xml:lang="en">ISBN</acronym> 9783030515836